Abnormal RNA stability in amyotrophic lateral sclerosis - E. M. Tank; C. Figueroa-Romero; L. M. Hinder; K. Bedi; H. C. Archbold; X. Li; K. Weskamp; N. Safren; X. Paez-Colasante; C. Pacut; S. Thumma; M. T. Paulsen; et al. (Nature Communications, 2018)
RNA instability may be a contributing factor in amyotrophic lateral sclerosis (ALS). Here the authors carry out genome-wide assessment of RNA synthesis and stability in cells derived from patients with C9orf72 ALS, sporadic ALS and healthy controls.